Analysis of anomalies in ADS-B and its GPS data - Ali, B.S.; Schuster, W.; Ochieng, W.; Majumdar, A. (Springer Verlag (Germany), 2016)
Traditionally, the surveillance component of the air traffic management system has been based on radar, which consists of two separate systems: primary radar and secondary radar, which both enable the measurement of the aircraft range and bearing to the radar station. Primary radar is based on signals emitted by a ground station simply being reflected off an object and detected by a ground-based receiver. Secondary radar also emits signals, but relies upon a transponder onboard the aircraft to emit a signal itself, modulated among others by a four-digit aircraft identity (Mode A), aircraft altitude (Mode C) and/or 24-bit unique address (Mode S). Typical accuracies of secondary radar are of the order of 0.03 NM in range and 0.07° in azimuth. However, no position integrity report is provided. Air traffic density is expected to significantly increase in the future. In order to maintain or enhance air travel efficiency, while maintaining safety, more accurate surveillance systems, with the required integrity, will be required. Automatic dependent surveillance–broadcast (ADS-B) is a new aviation surveillance system, envisioned to overcome the limitations of radar and to enhance surveillance performance and thereby increase airspace capacity. However, its high dependence on external systems such as onboard navigation and communication systems also increases the number of potential points of failure. It is important to understand and mitigate these failure modes before the system can reliably be implemented. The present study emerged as an exploratory research as part of a safety assessment framework development for the ADS-B system. It reviews the ADS-B failure modes, data collection and analysis of ADS-B and its corresponding onboard GPS data. The study identifies a set of failures common to certain aircraft models, with consistent error patterns. A key failure mode was found to be associated with the navigation data from the onboard GPS. We discuss the identified failure modes and investigate the nature and causes of these failures. The findings highlight some of the deficiencies of the current ADS-B system, which will need to be addressed before the ADS-B system can reliably be implemented.